2017
DOI: 10.1371/journal.pone.0179441
|View full text |Cite
|
Sign up to set email alerts
|

Change in potato consumption among Norwegian women 1998-2005—The Norwegian Women and Cancer study (NOWAC)

Abstract: Studies have shown that potato consumption in Norway have been on the decline in recent years. Increase in income and the association of potato consumption with weight gain and chronic diseases like type 2 diabetes have been identified as some of the factors responsible for the change. The aim of this study was to describe the change in potato consumption within persons and how non-dietary variables influenced that change among participants in the Norwegian Women and Cancer study (NOWAC). A prospective analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The reasons for the decline in potato consumption are varied and include changes in food preferences [ 7 ]. Potato consumption was recently examined in a Norwegian cohort of women who reported a 15% reduction in consumption from 1998 to 2005 [ 15 ]. Increase in income and a perceived association of potato consumption with weight gain and chronic diseases like type 2 diabetes mellitus (T2DM) have been identified as some of the factors responsible for the change, although low-carbohydrate, weight-reducing diets have given conflicting results [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for the decline in potato consumption are varied and include changes in food preferences [ 7 ]. Potato consumption was recently examined in a Norwegian cohort of women who reported a 15% reduction in consumption from 1998 to 2005 [ 15 ]. Increase in income and a perceived association of potato consumption with weight gain and chronic diseases like type 2 diabetes mellitus (T2DM) have been identified as some of the factors responsible for the change, although low-carbohydrate, weight-reducing diets have given conflicting results [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increase in income and a perceived association of potato consumption with weight gain and chronic diseases like type 2 diabetes mellitus (T2DM) have been identified as some of the factors responsible for the change, although low-carbohydrate, weight-reducing diets have given conflicting results [ 16 ]. Moreover, an increase in prevalence of T2DM has also been identified as a factor leading to a reduction in intake because of dietary advice [ 15 ]. However the nutritional benefits of the potato include a relatively high content of micronutrients such as potassium, vitamins such as the B vitamins, and fibre if the skin is eaten [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ek et al (2014) and Muraki et al (2016) associated the potato with weight gain and the risk of type 2 diabetes. But other studies contradict this: Linde et al (2006) found that potato consumption is not associated with obesity and Attah et al (2017) found that diabetes, overweight and obesity were associated with low potato consumption. Borch et al (2016) did a systematic review of the existing observational studies linking potatoes to obesity, diabetes and cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 96%
“…Potatoes are among the most consumed vegetables worldwide and among the most versatile and palatable of foods [1]. However, we have recently witnessed a decline in fresh potato consumption [2][3][4][5][6][7][8][9]. Several reasons, such as convenience, long cooking time, flavor, glycemic index, carb-free diets, income, generational changes, and busy lifestyle have been blamed for this decline [5,8,10].…”
Section: Introductionmentioning
confidence: 99%